Ética e psicologia analítica: articulações entre alteridade e psicologia em C. G. Jung e Emmanuel Lévinas - Carvalho, Antônio Gregory Rocha (2019)
The present study continues the research on the alterity and ethics in the psychologies initiated by Freire, admitting that the place of the Other is still an open question for the psychologies. Our problem thus translates into the fundamental Levinasian question about the place of the Other in Western thought that we address to Jung's analytical psychology, questioning to what extent the notion of ethics in Jung is traversed by the problem of the other. In this way, we proceed to a theoretical research articulating notions of the work of Jung and Emmanuel Lévinas. Our aim is to delimit the notion of ethics in Jung's Analytical Psychology and the role of alterity in this concept in articulation with the philosophy of radical alterity of Emmanuel Lévinas. We then proceed to the initial approach of the ethical problem for Jung, through which we identify the main concepts connected with this question - the problem of opposites, shadow, syzygy, self, unconscious and individuation - with which we work in view of a tentative interpretation for it. Afterwards, we discuss the articulation of these concepts with the Levinasian work, taking as a motto its concepts of God, Infinity and Face, and its philosophical branches more sensitive to the problem of otherness. Finally, our task is to pro-mote confrontation between the two perspectives, not to seek a synthesis, but to accentuate their proximities and their distances. In this way, we hope, in addition to seeking the objec-tives proposed here, to make evident the very manifest difference in this psychological dis-course before the Levinasian ethical debate. In fact, we seek to contribute to a scarce articula-tion in literature, that is, between Jung and Lévinas, and to the discussion of Jungian ethics. As a result, we find that, in Jung, ethics is a properly individual question, which cannot be solved by collective morality because it itself arises from the conflict between this moral code and individuality. Its resolution involves the openness and careful attention of the uncon-scious as psychic alterity and, therefore, must include the irrational factor. The Other, there-fore, marks his place in this psychology in both its concepts and its procedures. Moreover, the notion of the unconscious in this system denounces the limits of Western thought and implies scientific activity itself in the observation of this factor. Nonetheless, Jung distances himself from the notion of ethics as absolute responsibility for the Other as proposed by Lévinas, for he understands ethics as a consciously pursued relationship with psychic otherness in a dialec-tic with the social bond. The notion of responsibility in Jung, however, comes close to that of Lévinas, for he admits it as inescapable in front of the other as a psychic difference, in the foreground, and by the neighbor as a collectivity, secondly.